Composite material and preparation method and application thereof

By forming a high resistance composite structure on the silicon carbide epitaxial layer, the electric field ignition problem caused by electron migration of the silicon carbide epitaxial layer under high temperature conditions is solved, and the safety of semiconductor devices and the feasibility of industrial production is achieved.

CN118894727BActive Publication Date: 2024-12-13湖南德智新材料股份有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411378750.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2024-12-13
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

The high-speed migration of electrons under high temperature conditions causes electric field ignition, threatening the safety of semiconductor devices, and requiring increased resistance to hinder electron migration.

Method used

Using composite materials, including sintered silicon carbide and silicon carbide coatings attached to their surface, the coating consists of two layers: the first coating is columnar crystals, with a height (111) orientation, and the second coating also has a height (111) ) Orientation but lower degree of orientation than the first coating, combined with CVD deposition and heat treatment preparation, forming a structure with high resistance and low electron mobility.

Benefits of technology

It effectively improves the resistance of the silicon carbide epitaxial layer, prevents high electric field, avoids component ignition, and is suitable for semiconductor fields, with high process repeatability and suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118894727B_ABST
    Figure CN118894727B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of composite materials, and provides a composite material and a preparation method and application thereof, wherein the composite material comprises sintered silicon carbide and a silicon carbide coating attached to the surface of the sintered silicon carbide; the silicon carbide coating comprises a second coating and a first coating between the second coating and the sintered silicon carbide; the first coating is columnar crystals and presents a high (111) orientation; the second coating presents a high (111) orientation; the average particle size of the second coating is smaller than the average particle size of the first coating, and the resistivity of the composite material is 15-25 kΩ·cm. The composite material of the present invention has high resistance and low carrier mobility, and can effectively prevent the generation of a high electric field and avoid causing sparks in components.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of composite materials, and in particular to a composite material, a method for preparing the composite material, and application of the composite material in the semiconductor field. Background Art

[0002] Silicon carbide is an important wide bandgap semiconductor material with excellent electrical properties such as high electron saturation drift rate and breakdown field strength. In addition, due to its good mechanical, thermal and chemical stability, it can be used in semiconductor devices that serve under extreme conditions such as high temperature, high pressure and high frequency, such as semiconductor effect transistors and ultra-high power semiconductor devices.

[0003] In order to make silicon carbide materials adapt to various complex working environments, silicon carbide epitaxial materials have been developing in the direction of corrosion resistance, high temperature resistance, high strength and high breakdown field strength. Since SiC has the characteristics of a conductor under high temperature conditions, it causes high-speed migration of electrons to generate electric fields and sparks, which seriously threatens the safe use of many semiconductor devices. In order for the silicon carbide epitaxial layer to meet the requirements of engineering production applications, it is necessary to increase the resistance of the silicon carbide epitaxial layer, reduce its internal carrier concentration, reduce the carrier mobility, and increase its carrier lifetime. Therefore, increasing the resistance of the silicon carbide epitaxial layer and hindering the migration of electrons is an effective way to solve this problem. Summary of the invention

[0004] The purpose of the present invention is to provide a method for improving the resistance of a silicon carbide epitaxial layer, specifically to provide a composite material, and to provide a preparation method and application of the composite material. The silicon carbide coating on the surface of the composite material has high resistance and low electron mobility, which can effectively prevent the generation of a high electric field and avoid causing sparks in components.

[0005] In order to achieve the above-mentioned object, the first aspect of the present invention provides a composite material, which comprises sintered silicon carbide and a silicon carbide coating attached to the surface of the sintered silicon carbide, wherein the silicon carbide coating comprises a second coating and a first coating between the second coating and the sintered silicon carbide; the first coating is columnar and presents a high degree of (111) orientation, and in the first coating, the orientation degree of the (111) crystal plane is 0.7-0.9; the second coating presents a high degree of (111) orientation, and the orientation degree of the (111) crystal plane in the second coating is greater than 0.5 and lower than the orientation degree of the (111) crystal plane in the first coating; the average particle size of the grains in the first coating is 40μm-100μm, and the average particle size of the grains in the second coating is 10μm-30μm; the thickness of the silicon carbide coating is 80μm-120μm; the thickness of the first coating is 8μm-20μm; the resistivity of the composite material is 15-25kΩ·cm.

[0006] The second aspect of the present invention provides a method for preparing the composite material described in the first aspect, the method comprising: (1) performing a first deposition on the surface of sintered silicon carbide by a CVD method to obtain a preform comprising a first coating; (2) performing a second deposition on the surface of the first coating by a CVD method to obtain a precursor comprising a second coating; (3) heat treating the precursor to obtain a composite material; the conditions for the first deposition include: a deposition temperature of 1300-1500°C, a deposition pressure of 10 kPa-40 kPa, and a deposition time of 1-3 h; the conditions for the second deposition include: a deposition temperature of 900-1200°C, a deposition pressure of 20 kPa-80 kPa, and a deposition time of 4-8 h; the conditions for the heat treatment include: a temperature of 1500-1600°C and a time of 1-3 h.

[0007] The third aspect of the present invention provides application of the composite material as described above in the semiconductor field.

[0008] The present invention adopts the above technical solution to achieve the following beneficial effects:

[0009] (1) The composite material of the present invention contains sintered silicon carbide with high porosity and a silicon carbide coating attached to its surface, which makes it have high resistance and low electron mobility, and can effectively prevent the generation of high electric fields and avoid sparking of components. In addition, generally speaking, the impurity content inside sintered silicon carbide is relatively high, which makes it difficult to meet the high purity growth of silicon carbide epitaxial layer. In the present invention, the first coating is tightly combined with the surface of sintered silicon carbide, showing columnar crystal characteristics and a high degree of (111) orientation, which can completely cover the CVD silicon carbide with the sintered silicon carbide to ensure that its impurities will not volatilize in a high temperature environment.

[0010] (2) The preparation method provided by the present invention is simple and effective, suitable for large-scale industrial production, and has high process repeatability.

[0011] The endpoints and any values ​​of the range disclosed in this article are not limited to the precise range or value, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. Herein, in the absence of special instructions, data ranges include endpoints. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 Shown is a schematic structural diagram of the composite material prepared in Example 1 of the present invention.

[0013] Figure 2Shown is the XRD pattern of the first coating prepared in Example 1 of the present invention.

[0014] Figure 3 Shown is the XRD pattern of the second coating prepared in Example 1 of the present invention.

[0015] Reference numerals

[0016] 1. Sintered silicon carbide; 2. First coating; 3. Second coating. DETAILED DESCRIPTION

[0017] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0018] Unless otherwise defined, all scientific and technical terms used in the present invention have the same meanings as commonly understood by one of ordinary skill in the art to which the present invention relates.

[0019] A first aspect of the present invention provides a composite material, comprising sintered silicon carbide and a silicon carbide coating attached to the surface of the sintered silicon carbide, wherein the silicon carbide coating comprises a second coating and a first coating between the second coating and the sintered silicon carbide; the first coating is columnar and exhibits a high degree of (111) orientation, and in the first coating, the orientation degree of the (111) crystal plane is 0.7-0.9 (for example, 0.7, 0.75, 0.8, 0.85, 0.9); the second coating exhibits a high degree of (111) orientation, and the orientation degree of the (111) crystal plane in the second coating is greater than 0.5 (for example, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8 or more), and is lower than the orientation degree of the (111) crystal plane in the first coating; The average particle size of the grains in the first coating is 40μm-100μm (for example, 40μm, 50μm, 60μm, 70μm, 80μm, 90μm, 100μm), and the average particle size of the grains in the second coating is 10μm-30μm (for example, 10μm, 15μm, 20μm, 25μm, 30μm); the thickness of the silicon carbide coating is 80μm-120μm (for example, 80μm, 90μm, 100μm, 110μm, 120μm); the thickness of the first coating is 8μm-20μm (for example, 8μm, 10μm, 12μm, 14μm, 16μm, 18μm, 20μm); the resistivity of the composite material is 15-25kΩ·cm (for example, 15kΩ·cm, 17 kΩ·cm, 19 kΩ·cm, 21 kΩ·cm, 23 kΩ·cm, 25 kΩ·cm).

[0020] In the present invention, the use of high-porosity sintered silicon carbide is conducive to making the product have high resistance and low electron mobility, which can effectively prevent the generation of high electric fields and avoid causing sparks in components. The sintered SiC can be prepared by conventional methods in the art, such as by recrystallization sintering, and the sintered SiC can also be purchased commercially.

[0021] In some embodiments, the porosity of the sintered silicon carbide is 10-20% (eg, 10%, 12%, 14%, 16%, 18%, 20%).

[0022] In some embodiments, the surface roughness of the sintered SiC is 1 μm-5 μm, such as 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, and 5 μm.

[0023] In the present invention, the average particle size of the crystal grains is determined by scanning the coating with a scanning electron microscope (SEM) and measuring the SEM image using Image J software.

[0024] In the present invention, the high degree of (111) orientation refers to the directionality of the covalent crystal, and the SiC grains will grow along the (111) direction. The orientation degree of the (111) crystal plane is the ratio of the characteristic peak area of ​​the (111) crystal plane to the total area of ​​all characteristic peaks. In addition to the (111) crystal plane, the first coating and the second coating may also contain other crystal planes, such as the (200) crystal plane, the (220) crystal plane, the (311) crystal plane and the (110) crystal plane.

[0025] In some embodiments, the first coating surface comprises a (200) crystal plane, a (220) crystal plane, a (311) crystal plane, and a (110) crystal plane.

[0026] In some embodiments, in the first coating, the orientation degree of the (200) crystal plane is less than 0.05, the orientation degree of the (220) crystal plane is 0.05-0.1, the orientation degree of the (311) crystal plane is 0.05-0.1, and the orientation degree of the (110) crystal plane is less than 0.05.

[0027] In some embodiments, the second coating surface comprises a (200) crystal plane, a (220) crystal plane, a (311) crystal plane, and a (110) crystal plane.

[0028] In some embodiments, in the second coating, the orientation degree of the (200) crystal plane is less than 0.15, the orientation degree of the (220) crystal plane is less than 0.25, the orientation degree of the (311) crystal plane is less than 0.25, and the orientation degree of the (110) crystal plane is less than 0.05.

[0029] In the present invention, the orientation degree can be obtained by XRD testing.

[0030] In some embodiments, the second coating has a thickness of 60 μm-110 μm, such as 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, or 110 μm.

[0031] In some embodiments, the thickness ratio of the first coating layer to the second coating layer is 1:3-15, such as 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:12, 1:14, or 1:15.

[0032] The second aspect of the present invention provides a method for preparing the composite material described in the first aspect, the method comprising: (1) performing a first deposition on the surface of sintered silicon carbide by a CVD method to obtain a preform comprising a first coating; (2) performing a second deposition on the surface of the first coating by a CVD method to obtain a precursor comprising a second coating; (3) heat treating the precursor to obtain a composite material; the conditions of the first deposition include: a deposition temperature of 1300-1500°C (for example, 1300°C, 1350°C, 1400°C, 1450°C, 1500°C), a deposition pressure of 10 kPa-40 kPa (for example, 10 kPa, 15 kPa, 20 kPa, 25 kPa, 30 kPa, 35 kPa, 40 kPa), and a deposition time of 1-3 h (for example, 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h, 13 h, 14 h, 15 h, 16 h, 17 h, 18 h, 19 h, 20 h, 21 h, 22 h, 23 h, 24 h, 25 h, 26 h, 27 h, 28 h, 29 h, 30 h, 31 h, 32 h, 33 h, 34 h, 35 h, 36 h, 37 h, 38 h, 39 h, 40 h, 41 h, 42 h, 43 h, 44 h, 45 h, 46 h, 47 h, 48 h, 49 h, 50 h, 51 h, 52 h, 53 h h, 3h); the conditions for the second deposition include: a deposition temperature of 900-1200°C (for example, 900°C, 1000°C, 1100°C, 1200°C), a deposition pressure of 20 kPa-80 kPa (for example, 20 kPa, 30 kPa, 40 kPa, 50 kPa, 60 kPa, 70 kPa, 80kPa), and a deposition time of 4-8h (for example, 4h, 5h, 6h, 7h, 8h); the conditions for the heat treatment include: a temperature of 1300-1600°C (for example, 1300°C, 1350°C, 1400°C, 1450°C, 1500°C, 1550°C, 1600°C), and a time of 1-3h (for example, 1h, 1.5h, 2h, 2.5h, 3h).

[0033] In some embodiments, the method further includes pre-treating the material to be deposited (such as sintered silicon carbide or preform) before deposition to remove surface impurities. The pre-treatment method is pickling. The pickling acid can be a conventional acid in the art, such as hydrofluoric acid, hydrochloric acid and sulfuric acid, and the concentration of the acid can be selected in a wide range, such as 40-60wt%. The pickling time can be 0.5-2h.

[0034] It should be understood that the pretreatment may also be combined with operations such as ultrasonic treatment, rinsing or drying. The drying method may be a conventional drying method, such as drying using a vacuum dryer or air blowing (drying at 100-300°C for more than 2 hours).

[0035] In the present invention, the deposition equipment used in the CVD deposition process can be a CVD vapor deposition furnace. The material to be deposited can be placed horizontally in the deposition reaction chamber, the furnace door can be closed, the reaction chamber can be evacuated to below 200Pa, and then the temperature can be increased to the deposition temperature at 3°C / min-6°C / min.

[0036] In some embodiments, the gas system for the first deposition and the gas system for the second deposition each independently comprise trichloromethylsilane (CH 3 SiCl 3 (ie MTS) and hydrogen and optionally a diluent gas.

[0037] In some embodiments, in the gas system used for the first deposition, the flow ratio of trichloromethylsilane to hydrogen is 1:5-15, for example, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12, 1:13, 1:14, 1:15.

[0038] During the first deposition process, a diluent gas such as argon and / or helium may be introduced. The amount of argon may be selected within a wide range, for example, the flow ratio of hydrogen to argon is 1-10:1, such as 1:1, 2:1, 4:1, 6:1, 8:1, 10:1.

[0039] After the first deposition is completed, the introduction of trichloromethylsilane and hydrogen may be stopped, and argon may be continuously introduced for a temperature reduction treatment.

[0040] In some embodiments, in the gas system used for the second deposition, the flow ratio of trichloromethylsilane to hydrogen is 1:10-40, such as 1:10, 1:15, 1:20, 1:25, 1:30, 1:35, or 1:40.

[0041] If not otherwise specified, in the present invention, the temperature can be raised to the target temperature at 3-6°C / min, and can be lowered to the target temperature at 10-15°C / min.

[0042] In some embodiments, the deposition rate of the first coating is 2-8 μm / h, such as 2 μm / h, 4 μm / h, 6 μm / h, 8 μm / h, and the deposition rate of the second coating is 15-30 μm / h, such as 15 μm / h, 20 μm / h, 25 μm / h, 30 μm / h.

[0043] The third aspect of the present invention provides application of the composite material as described above in the semiconductor field.

[0044] The composite material can be used as a silicon carbide epitaxial material and has the characteristics of high resistance and low electron mobility.

[0045] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0046] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0047] The present invention is described in detail below in conjunction with specific embodiments, which are used to understand but not to limit the present invention.

[0048] In the following examples, the average grain size is determined by scanning electron microscopy (SEM), and the grain size is determined according to the scale of the scanning electron microscope; the crystal plane orientation is determined by XRD.

[0049] Example 1

[0050] This example is used to illustrate the preparation method of the composite material of the present invention.

[0051] (1) A sintered silicon carbide substrate (roughness 2.4 μm) with a porosity of 17.9% was placed in a chemical vapor deposition device, evacuated, and then heated by introducing argon gas, with the temperature increased to 1420°C at a rate of 5°C / min.

[0052] (2) The reaction gases MTS and hydrogen were introduced, and argon was introduced at the same time, and the deposition process parameters were controlled as follows: deposition temperature was 1420 °C, deposition pressure was 25 kPa, and deposition time was 2 h. Among them, the flow rate of MTS was 60 g / min, the flow rate of hydrogen was 108 L / min, and the flow rate of argon was 72 L / min.

[0053] After the deposition is completed, the reaction gas is stopped and argon gas is continuously introduced to cool the coating to obtain the first coating. The first coating has relatively large grains and presents columnar crystal characteristics as a whole. The average grain size is about 80 μm and the coating thickness is about 10 μm. Figure 2 As shown, its surface presents a high degree of (111) orientation with an orientation degree of 0.88. The (200) crystal plane, (220) crystal plane, (311) crystal plane and (110) crystal plane are less oriented with orientation degrees of 0.01, 0.04, 0.05 and 0.02 respectively.

[0054] (3) The surface of the first coating is pickled, and surface impurities are removed by ultrasound. The substrate is then placed in a CVD furnace for secondary deposition to obtain a second coating. The deposition process parameters are: deposition temperature of 1080°C, deposition pressure of 52 kPa, and deposition time of 4 h. The flow rate of MTS is 45 g / min, the flow rate of hydrogen is 170 L / min, and the flow rate of argon is 115 L / min.

[0055] The thickness of the second coating layer reaches 90 μm, and the average size of the second coating layer is about 24 μm. Its crystal plane orientation is affected by the first coating layer and also presents a high degree of (111) orientation. Figure 3 As shown, the orientation degree of the (111) crystal plane is 0.55; the orientation degrees of the (200), (220) and (311) planes are 0.05, 0.2 and 0.2 respectively.

[0056] (4) The deposited material is heat treated to obtain a composite material, wherein the heat treatment temperature is 1550°C and the time is 2 hours. The structural schematic diagram of the obtained composite material is shown in Figure 1 As shown, from the inside to the outside, it includes sintered silicon carbide, a first coating layer and a second coating layer.

[0057] Example 2

[0058] This example is used to illustrate the preparation method of the composite material of the present invention.

[0059] (1) A sintered silicon carbide substrate (roughness 1.9 μm) with a porosity of 15.6% was placed in a chemical vapor deposition device, evacuated, and then heated by introducing argon gas, with the temperature increased to 1370°C at a rate of 5°C / min.

[0060] (2) The reaction gases MTS and hydrogen were introduced, and argon was introduced at the same time, and the deposition process parameters were controlled as follows: deposition temperature was 1370°C, deposition pressure was 30 kPa, and deposition time was 2 h. Among them, the flow rate of MTS was 100 g / min, the flow rate of hydrogen was 120 L / min, and the flow rate of argon was 80 L / min.

[0061] After the deposition is completed, the reaction gas is stopped and argon is continuously introduced for cooling treatment to obtain the first coating. The first coating has large grains and exhibits columnar crystal characteristics as a whole. The average grain size is between 50 μm and the coating thickness is about 14 μm. Its surface exhibits a high degree of (111) orientation with an orientation degree of 0.80. The (200) crystal plane, (220) crystal plane, (311) crystal plane and (110) crystal plane are less oriented with orientation degrees of 0.01, 0.08, 0.09 and 0.02 respectively.

[0062] (3) The surface of the first coating is pickled, and surface impurities are removed by ultrasound. The substrate is then placed in a CVD furnace for secondary deposition to obtain a second coating. The deposition process parameters are: deposition temperature of 1030°C, deposition pressure of 60 kPa, and deposition time of 4 h. The flow rate of MTS is 60 g / min, the flow rate of hydrogen is 190 L / min, and the flow rate of argon is 125 L / min.

[0063] The thickness of the second coating layer reached 93 μm, and the average size of the second coating layer was about 18 μm. Its crystal plane orientation was affected by the first coating layer and also showed a high degree of (111) orientation. The orientation degree of the (111) crystal plane was 0.52; the orientation degrees of the (200) crystal plane, (220) crystal plane and (311) crystal plane were 0.04, 0.22 and 0.22 respectively.

[0064] (4) The deposited material is heat treated to obtain a composite material, wherein the heat treatment temperature is 1550° C. and the time is 2 h.

[0065] Example 3

[0066] This example is used to illustrate the preparation method of the composite material of the present invention.

[0067] (1) A sintered silicon carbide substrate (roughness 3.1 μm) with a porosity of 19.8% was placed in a chemical vapor deposition device, evacuated, and then heated by introducing argon gas, with the temperature increased to 1470°C at a rate of 5°C / min.

[0068] (2) The reaction gases MTS and hydrogen were introduced, and argon was introduced at the same time, and the deposition process parameters were controlled as follows: deposition temperature was 1470°C, deposition pressure was 20 kPa, and deposition time was 2 h. Among them, the flow rate of MTS was 50 g / min, the flow rate of hydrogen was 108 L / min, and the flow rate of argon was 72 L / min.

[0069] After the deposition is completed, the reaction gas is stopped and argon is continuously introduced for cooling treatment to obtain the first coating. The first coating has large grains and exhibits columnar crystal characteristics as a whole. Its average grain size is about 70 μm and the coating thickness is about 9 μm. Its surface exhibits a high degree of (111) orientation with an orientation degree of 0.85. The (200), (220), (311) and (110) crystal planes have less orientation with orientation degrees of 0.01, 0.05, 0.06 and 0.03 respectively.

[0070] (3) The surface of the first coating is pickled, and surface impurities are removed by ultrasound. The substrate is then placed in a CVD furnace for secondary deposition to obtain a second coating. The deposition process parameters are: deposition temperature of 1130°C, deposition pressure of 42 kPa, and deposition time of 4 h. The flow rate of MTS is 40 g / min, the flow rate of hydrogen is 168 L / min, and the flow rate of argon is 112 L / min.

[0071] The thickness of the second coating layer reached 94 μm, and the average size of the second coating layer was about 21 μm. The orientation of its crystal plane was affected by the first coating layer and also showed a high degree of (111) orientation. The orientation degree of the (111) crystal plane was 0.59; the orientation degrees of the (200) crystal plane, (220) crystal plane and (311) crystal plane were 0.05, 0.18 and 0.18 respectively.

[0072] (4) The deposited material is heat treated to obtain a composite material, wherein the heat treatment temperature is 1550° C. and the time is 2 h.

[0073] Comparative Example 1

[0074] The method described in Example 1 was followed, except that a dense SiC substrate (porosity 0.5%) was used instead of the sintered silicon carbide substrate.

[0075] Comparative Example 2

[0076] The operation is carried out according to the method described in Example 1, except that the temperature of the first deposition is different and the conditions of the second deposition remain unchanged.

[0077] Comparative Example 2a: The first deposition temperature is 1600° C. The first coating layer of the obtained composite material exhibits a hexagonal crystal structure as a whole (transformed from β-SiC to α-SiC).

[0078] Comparative Example 2b: The first deposition temperature is 1200° C. The first coating layer of the obtained composite material has a cauliflower-like crystal morphology as a whole, and the average grain size is about 2.4 μm.

[0079] Comparative Example 2c: The first deposition temperature is 1000° C. The first coating layer of the obtained composite material has no morphology.

[0080] Comparative Example 3

[0081] The operation is carried out according to the method described in Example 1, except that the conditions of the second deposition are different.

[0082] Comparative Example 3a: The temperature and pressure of the second deposition were the same as those of the first deposition. The second coating obtained showed large-sized columnar crystals as a whole, with an average grain size of 80 μm, and a (111) orientation on the surface with an orientation degree of 0.88.

[0083] Comparative Example 3b: The temperature of the second deposition was different, namely 1300°C. The obtained second coating had a tetragonal crystal shape as a whole, an average grain size of 30 μm, a (111) orientation on the surface, and an orientation degree of 0.80.

[0084] Comparative Example 3c: The second deposition temperature was different, 800°C, and the obtained second coating had no morphology.

[0085] Comparative Example 4

[0086] The method described in Example 1 is followed, except that the first deposition is not performed, only the second deposition is performed, and the time of the second deposition is extended so that the thickness of the obtained silicon carbide coating is the sum of the first coating and the second coating in Example 1.

[0087] Comparative Example 5

[0088] This comparative example is used to illustrate the preparation method of the reference composite material.

[0089] The method described in Example 1 is followed, except that no heat treatment is performed after the coating is obtained by sintering. Because the purity of sintered silicon carbide can only reach 99.9%, while the coating part needs to reach more than 99.999%, the presence of metal impurities will result in the inability to generate SiC crystals of qualified purity due to the lack of heat treatment (because one of the purposes of heat treatment is to remove metal impurities), and the second coating obtained has no crystalline form as a whole.

[0090] Test Case

[0091] The resistivity test was performed on the composite materials prepared in the examples and comparative examples.

[0092] The resistivity of the composite material was determined with reference to GB_T 31838.2-2019 Dielectric and resistive properties of solid insulating materials Part 2 Resistive properties (DC method) Volume resistance and volume resistivity. The results are shown in Table 1.

[0093] Table 1

[0094]

[0095] It can be seen from the above data that, compared with the comparative example, the composite material prepared by the method described in the present invention has a significantly higher resistivity, which is beneficial for effectively preventing the generation of high electric fields and avoiding sparks in components.

[0096] It should be noted that, in this article, the terms "comprise", "include" or any other variant thereof are intended to cover non-exclusive inclusion, so that the process, method, article or device including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise one..." do not exclude the presence of other identical elements in the process, method, article or device including the element. In addition, it should be pointed out that the scope of the methods and devices in the embodiments of the present application is not limited to performing functions in the order shown or discussed, and may also include performing functions in a substantially simultaneous manner or in reverse order according to the functions involved, for example, the described method may be performed in an order different from that described, and various steps may also be added, omitted, or combined. In addition, the features described with reference to certain examples may be combined in other examples.

[0097] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A composite material, It is characterized in that The composite material includes sintered silicon carbide and a silicon carbide coating attached to the surface of the sintered silicon carbide, wherein the silicon carbide coating includes a second coating and a first coating between the second coating and the sintered silicon carbide; The first coating layer is columnar crystals and presents a high degree of (111) orientation, and in the first coating layer, the orientation degree of the (111) crystal plane is 0.7-0.9; The second coating layer is highly (111) oriented, and the orientation degree of the (111) crystal plane in the second coating layer is greater than 0.5 and lower than the orientation degree of the (111) crystal plane in the first coating layer; The average particle size of the grains in the first coating is 40 μm-100 μm, and the average particle size of the grains in the second coating is 10 μm-30 μm; The thickness of the silicon carbide coating is 80 μm-120 μm; the thickness of the first coating is 8 μm-20 μm; The resistivity of the composite material is 15-25 kΩ·cm.

2. The composite material according to claim 1, It is characterized in that The first coating surface comprises a (200) crystal plane, a (220) crystal plane, a (311) crystal plane and a (110) crystal plane; The surface of the second coating layer includes a (200) crystal plane, a (220) crystal plane, a (311) crystal plane and a (110) crystal plane.

3. The composite material according to claim 2, It is characterized in that In the first coating, the orientation degree of the (200) crystal plane is less than 0.05, the orientation degree of the (220) crystal plane is 0.05-0.1, the orientation degree of the (311) crystal plane is 0.05-0.1, and the orientation degree of the (110) crystal plane is less than 0.05; In the second coating, the orientation degree of the (200) crystal plane is less than 0.15, the orientation degree of the (220) crystal plane is less than 0.25, the orientation degree of the (311) crystal plane is less than 0.25, and the orientation degree of the (110) crystal plane is less than 0.

05.

4. The composite material according to any one of claims 1 to 3, It is characterized in that The porosity of sintered silicon carbide is 10-20%; The thickness ratio of the first coating layer to the second coating layer is 1:3-15.

5. A method for preparing the composite material according to any one of claims 1 to 4, It is characterized in that The method includes: (1) performing a first deposition on the surface of sintered silicon carbide by a CVD method to obtain a preform including a first coating; (2) performing a second deposition on the surface of the first coating layer by a CVD method to obtain a precursor comprising the second coating layer; (3) heat treating the precursor to obtain a composite material; The conditions of the first deposition include: a deposition temperature of 1300-1500° C., a deposition pressure of 10 kPa-40 kPa, and a deposition time of 1-3 h; The conditions of the second deposition include: a deposition temperature of 900-1200° C., a deposition pressure of 20 kPa-80 kPa, and a deposition time of 4-8 h; The heat treatment conditions include: temperature of 1300-1600° C. and time of 1-3 hours.

6. The method according to claim 5, It is characterized in that The gas system for the first deposition and the gas system for the second deposition each independently contain trichloromethylsilane and hydrogen and optionally a diluent gas.

7. The method according to claim 6, It is characterized in that In the gas system used for the first deposition, the flow ratio of trichloromethylsilane to hydrogen is 1:5-15; In the gas system used for the second deposition, the flow ratio of trichloromethylsilane to hydrogen is 1:10-40.

8. The method according to claim 6, It is characterized in that The dilution gas is argon and / or helium.

9. The method according to claim 6, It is characterized in that In the gas system for the first deposition and the gas system for the second deposition, the flow ratio of hydrogen gas to the diluent gas is independently 1-10:

1.

10. Use of the composite material according to any one of claims 1 to 4 in the semiconductor field.